Design and Construction of Screw Type Oil Press Equipment - Van Dedo Pasaribu; Ainu Rohanah; Nazif Ichwan (Universitas Sumatera Utara, 2014)
Compression process is an important step in candlenut oil production, which in this process will be produced candlenut oil through heating and pressing candlenut. Utilization of candlenut oil today more and more, not only in the food industry but also in the cosmetic, paint, as well as fuels alternative. This study was aimed to plan and builda screw mechanical device of candlenut pressing. The study was conducted with literature study, experiment, observation and testing of the equipment. The parameters measured were the effective capacity of the equipment. The results showed that the effective capacity of the oil press was 3,35kg/hour. Key word: candlenut, capacity, postharvest equipment, pressing, effective